PaDef defensin from avocado (Persea americana var. drymifolia) is cytotoxic to K562 chronic myeloid leukemia cells through extrinsic apoptosis. (June 2018) - Flores-Alvarez, Luis José; Guzmán-Rodríguez, Jaquelina Julia; López-Gómez, Rodolfo; Salgado-Garciglia, Rafael; Ochoa-Zarzosa, Alejandra; López-Meza, Joel E.
Highlights: PaDef defensin from avocado shows cytoxicity on K562 chronic myeloid leukemia cells. PaDef defensin did not affect human normal peripheral blood mononuclear cells. K562 membrane potential or calcium flow was not affected by PaDef defensin. Cytotoxic effects on K562 cells of PaDef are due to the induction of extrinsic apoptosis. Abstract: Plant defensins, a group of antimicrobial peptides, show selective cytotoxicity toward cancer cells. However, their mechanisms of action remain poorly understood. Here, we evaluated the cytotoxicity of PaDef defensin from avocado ( Persea americana var. drymifolia) on K562 chronic myeloid leukemia cells and analyzed the pathway involved in the induction of cell death. The defensin PaDef was not cytotoxic against human PBMCs; however, it was cytotoxic for K562 cell line (IC50 = 97.3 μg/ml) activating apoptosis at 12 h. PaDef did not affect the mitochondrial membrane potential (ΔΨm), neither the transmembranal potential or the release of intracellular calcium. Also, PaDef induced gene expression of caspase 8 (∼2 fold), TNF-α (∼4 fold) and TNFR1 (∼10 fold). In addition, the activation of caspase 8 was detected at 24 h, whereas caspase 9 activity was not modified, suggesting that the extrinsic apoptosis pathway could be activated. In conclusion, PaDef induces apoptosis on K562 cells, which is related to the activation of caspase 8 and involves the participation of TNF-α, which is a novel property for a plant defensin.